ENHANCING SELF-CONFIDENCE IN SPEAKING SKILLS AMONG MIDDLE-AGED STUDENTS THROUGH EDUCATIONAL TECHNOLOGIES - Egamberganova Gulnoza Ulug'bek qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
This article explores how educational technologies can enhance self-confidence in speaking skills among these students. By integrating interactive applications, virtual classrooms, and gamified learning experiences into the curriculum, educators can create supportive environments that encourage practice and reduce anxiety. Case studies demonstrate the effectiveness of these technologies in improving students’ speaking abilities. The article concludes by emphasizing the importance of equitable access to technology and professional development for teachers to maximize the benefits of these tools. Effective communication is crucial for academic and personal success, particularly for students in elementary schools  who are developing their speaking skills. However, many students face challenges related to speaking anxiety, which can hinder their participation in class and limit their language development.